2007
DOI: 10.1159/000101027
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study to Compare Subcutaneously Buried Peritoneal Dialysis Catheter Technique with Conventional Technique

Abstract: Aims: To reduce peritoneal dialysis-related infections, Moncrief-Popovich (MP) designed a special catheter and implantation technique. Herein we report our experience of patients treated with the MP and conventional approach. Methods: A total of 214 patients were divided into three groups according to catheter type and implantation technique: group A received a MP catheter (MPC) via MP technique (n = 27); group B received Tenckhoff catheters via MP technique (n = 32), and group C received Tenckhoff catheters v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…Data presented in a prospective study looking at subcutaneously buried versus unburied catheter placement technique showed an overall similar risk of peritonitis development [17] . Comparable findings were reported by another prospective study investigating the Moncrief-Popovich design and insertion technique, showing no difference in incidence of peritonitis [18] . Another observational study showed a reduced rate of surgical, mechanical, and infectious complications with the buried placement technique, although the primarily descriptive nature of the study limited its validity as well as reproducibility [19] .…”
Section: Discussionsupporting
confidence: 72%
“…Data presented in a prospective study looking at subcutaneously buried versus unburied catheter placement technique showed an overall similar risk of peritonitis development [17] . Comparable findings were reported by another prospective study investigating the Moncrief-Popovich design and insertion technique, showing no difference in incidence of peritonitis [18] . Another observational study showed a reduced rate of surgical, mechanical, and infectious complications with the buried placement technique, although the primarily descriptive nature of the study limited its validity as well as reproducibility [19] .…”
Section: Discussionsupporting
confidence: 72%
“…The novel aspect of this technique was the potential reduction in exit-site and peritoneal infections because of the lack of an exit site (which serves as an entry port for bacteria) and the elimination of biofilm. Notwithstanding the initial motives, the MP technique has not consistently been shown to lower the incidence of PD-related infections (3-10). However, the technique does offer several potential advantages: it is more cost-effective, because follow-up clinic visits and catheter flushing are unnecessary; it applies to PD the concept of early access that is analogous to the arteriovenous fistula in hemodialysis (11); and subcutaneous burial of the distal portion of the catheter may be more cosmetically acceptable to patients.…”
mentioning
confidence: 99%
“…A larger series by Wu et al. 7, 5 comprising 214 participants supports this with the finding that catheter survival and peritonitis rates were similar in those who received buried and non-buried catheters. This study, however, did find that there was a trend towards a reduced healthcare cost associated with buried catheters.…”
Section: Discussionmentioning
confidence: 78%